The effect of magnetic field on the activity of superoxide dismutase - Büyükuslu, Nihal; ATAK, ÇİMEN; ÇELİK, ÖZGE (Haliç University, Faculty of Arts and Sciences, Department of Molecular Biology and Genetics, Fındıkzade 34280, İstanbul-Turkey, 2006)
The effects of magnetic field on superoxide dismutase activity were investigated. All living systems are affected by magnetic field and electromagnetic field in a way of their response systems. Since magnetic field has an impact on biochemical reactions that involve more than one unpaired electron, in our study SOD activity, one of the enzyme responsible for antioxidant system, was measured under magnetic fields using an apparatus explained at material methods. There has been a significant increase of SOD activity when passed 0, 1, 9 and 15 times at 2.9-4.6 mT magnetic field density for 0, 2.2, 19.8 and 33.0 seconds respectively.

Superoksit dismutaz aktivitesi üzerine manyetik alan etkileri araflt›r›lm›flt›r. Bütün yaflayan sistemler, yan›t sistemlerine ba¤l› olarak elektrik ve manyetik alan ve elektromanyetik alandan etkilenirler. Manyetik alan, ortaklamam›fl elektron içeren biyokimyasal reaksiyonlar üzerinde etkili oldu¤undan, çal›flmam›zda, antioksidan sistemlerinden biri olan, SOD aktivitesi manyetik alan alt›nda ölçüldü. 2.9-4.6 mT da 0, 1, 9 ve 15 kez, s›ras›yla 0, 2.2, 19.8 ve 33.0 sn lik zamanlarda geçirildi¤inde SOD aktivitesinde önemli bir art›fl tespit edildi.
Keywords: Superoxide dismutase; magnetic field; enzyme activity; Süperoksit dismutaz; manyetik alan; enzim aktivitesi